Adipose Tissue-Derived Extracellular Vesicles: A Promising Biomarker and Therapeutic Strategy for Metabolic Disorders - Wenhui Liu; Tianyan Liu; Qingyu Zhao; Junqiu Ma; Jiajia Jiang; Hui Shi (Stem Cells International)
Adipose tissue plays an important role in systemic energy metabolism, and its dysfunction can lead to severe metabolic disorders. Various cells in adipose tissue communicate with each other to maintain metabolic homeostasis. Extracellular vesicles (EVs) are recognized as novel medium for remote intercellular communication by transferring various bioactive molecules from parental cells to distant target cells. Increasing evidence suggests that the endocrine functions of adipose tissue and even the metabolic homeostasis are largely affected by different cell-derived EVs, such as insulin signaling, lipolysis, and metabolically triggered inflammation regulations. Here, we provide an overview focused on the role of EVs released by different cell types of adipose tissue in metabolic diseases and their possible molecular mechanisms and highlight the potential applications of EVs as biomarkers and therapeutic targets. Moreover, the current EVs-based therapeutic strategies have also been discussed. This trial is registered with NCT05475418.